Policy Demands on Promoting Physical Activity for College Students in China - Wang, Xinghua; Song, Guandong (Technium Social Sciences Journal, 2023)
In China's current higher education environment, the normalization of sedentary behavior makes college students a typical population with an inactive lifestyle. In order to effectively promote physical activity behaviors among college students, it is necessary to develop physical activity policies for college students in China. By investigating the physical activity level of Chinese college students, this study verifies the necessity of promoting physical activity in college students. Moreover, the present study analyzes the situation of policy demand from three aspects: policy content demand, policy effectiveness demand, and policy non-mandatory demand. The findings show there are policy demands on (1) policy content supplementation in college settings, (2) policy effectiveness based on the assumption of “limited rationality,” and (3) giving the freedom of decision-making. This study can provide reliable advice for policymakers on physical activity for college students in China.